THE CONTRIBUTION OF PERCEIVED ORGANIZATIONAL SUPPORT TO JOB SATISFACTION THROUGH THE ROLE OF WORK ENGAGEMENT AMONG ACADEMICS AT PRIVATE UNIVERSITIES - Pemilia Sulistyowati; Tri Imaliya; Diah Kusumawati; Hifa Labiba Afi Huwaida (ITB AAS Indonesia Surakarta, 2025)
Organization support enhances work engagement, thus enhances employee job satisfaction. This research is targeted to testing the effect of job satisfaction from perceived organizational support through work engagement among all lectures at private universities in Central Java Province. The methodology applied in this work is an associative method with a quantitative bias. Samples used purposive sampling technique to take 100 respondents from the entire lecturers who worked at private universities in Central Java Province. The questionnaires were used for collection of data and rated with Likert scale. The method of the data analysis was SEM-PLS and testing the databy using SmartPLS software version 4.1.1.2. There are two stages in the SEM-PLS analysis, an outer model and an inner model. The findings showed that the job satisfaction is significantly affected by the perceived organizational support (POS). It is further established that there is mediating impact of the variable work engagement on the relationship between the variable perceived organizational support and job satisfaction.